Pathways to mental health care in Italy: Results from a multicenter study. (August 2014) - Volpe, Umberto; Fiorillo, Andrea; Luciano, Mario; Del Vecchio, Valeria; Palumbo, Claudia; Calò, Salvatore; Piras, Sara; Signorelli, Maria; Filippo, Dario; Piselli, Massimiliano; De Fazio, Pasquale; Gotelli, Simona; et al.
Background and aims: In Italy, the reform of the mental health system in 1978 should have drastically changed the provision of care and pathways of patients seeking to obtain it. The aim of this article is to examine the current pathways to psychiatric care in Italy. Methods: We used a method developed in the World Health Organization international collaborative studies to investigate pathways to care in 15 Italian mental health centers. We recruited 420 patients with a psychiatric illness and explored the care pathways they took to reach to psychiatric services and the delays from the onset of illness to reaching psychiatric care. Results: The majority of patients (33.8%) had direct access to mental health care, whereas the others arrived to a specialist in psychiatry through general hospitals (20.3%), general practitioners (33.0%) or private practitioners (9.8%). The main diagnosis for referral was neurotic disorder (36.6%), followed by affective disorder (35.4%) and psychotic disorder (11.5%). The delay from onset of illness to psychiatric care was greater for patients with psychotic disorders than for those with affective and neurotic disorders. The most frequently prescribed treatments were pharmacotherapy (56%), psychological support (8%), and psychotherapy (7.0%); 15% of the patients received no treatment. Conclusions: Our multicenter study shows that although general practitioners and hospital doctors are still the main referral point for mental health care, a greater proportion of patients are first seen in private settings or directly reach mental health centers, compared to previous surveys conducted in Italy. However, a stronger collaboration of psychiatrists with general practitioners and psychologists is still needed.